Corporate Political Funding in India: A Need for Reform - Sandeep Khakase; Manika Kamthan Somthankar (Review of International Economic, Taxation, and Regulations, 2025)
Indian political parties have been financed largely by companies for their expenses. Indeed, such funding or donations or charities are regulated or governed under distinct laws. In the last decade, India has witnessed several amendments pertaining to corporate’s political funding; some are made in the name of transparency or for other reasons. Despite several claims, existing Indian laws related to political funding are ambiguous and hazy. Hence, there is an immense need to understand the regulatory or legal framework of political funding which is discussed briefly in this article. While discussing corporate donation, there are many questions related to shareholder’s interest: why companies should pay political donations out of shareholder’s money, secondly, how can the board of directors donate shareholder’s money? Lastly, will it be possible to achieve transparency in political funding? This paper aimed to answer these questions, identifying the need for reforms. In this study, a method of prevailing literature reviews and legislative analysis is used. Researcher concluded that donation is taking away a part of profit of a company hence, declines shareholders value. I implies a need to reform the laws including putting threshold of 5%, shareholder’s resolution for donation, removing anonymity created by Electoral Bonds and restricting foreign funding. This paper intended the Indian governments and policy makers to revisit the laws. Though, scope of this paper is limited to India, it has addressed a global concern of political donation.